Contact Interaction of Chromium Diboride with Nickel-Matrix Self-Fluxing Alloy - Umanskyi, O.P.; Storozhenko, M.S.; Terentiev, O.Ye; Krasovskyy, V.P.; Tarelnyk, V.B.; Martsynkovskyy, V.S.; Martsenyuk, I.S.; Gubin, Yu.V. (Powder metallurgy and metal ceramics, 2022)
Contact interaction of the nickel-matrix self-fluxing NiCrBSiC eutectic alloy with hot-pressed chromium diboride ceramics was studied by the sessile drop method in vacuum at 1100°C. The structure and phase composition of the starting alloy were examined. Chemical interaction between components in the NiCrBSiC system was found to occur in the melting process to promote a heterophase structure consisting of chromium carbide and boride grains distributed in the metallic matrix. The composite rather than the alloy took part in the wetting of chromium diboride. The wetting kinetics in the NiCrBSiC–CrB 2 system was studied. The self-fluxing NiCrBSiC alloy was shown to wet CrB 2 to form contact angle θ = 17°. Intensive chemical interaction between the alloy and substrate chemical elements was observed in the NiCrBSiC–CrB 2 system. The distribution of chemical elements in the interaction area of the NiCrBSiC–CrB 2 system was analyzed. Chromium was an interfacially active element in this system, and contact interaction proceeded through dissolution of the CrB 2 ceramics along the grain boundaries simultaneously with penetration of the nickel-matrix alloy. The contact interaction resulted in CrB and Cr 2 B with lower microhardness than that of CrB 2 . Interaction in the NiCrBSiC–CrB 2 system is unpredictable and changes the ceramic composition, resulting in decrease in the composite microhardness. Therefore, the use of CrB 2 particles as reinforcing additives for the self-fluxing NiCrBSiC alloy to produce composite powders for thermal spray coatings with high wear resistance is not reasonable.